The Effect of Room Facilities on Guest Satisfaction while Staying at Gran Malindo Hotel Bukittinggi - Akbar, Maulana; Manvi, Kurnia Illahi (JURNAL PENDIDIKAN DAN KELUARGA, 2024)
This research is motivated by the presence of guests who are dissatisfied with the room facilities of Gran Malindo Hotel Bukittinggi so that it can affect guest satisfaction while staying at Gran Malindo Hotel Bukittinggi, which causes guest loyalty to be low as well as room occupancy rates that have not reached the target. This study aims to analyze the effect of room facilities on guest satisfaction while staying at the Gran Malindo Hotel Bukittinggi. This research is classified as quantitative research with a causal associative approach. The study population was all guests who stayed at Gran Malindo Hotel Bukittinggi during January–June 2021. The total sample in this study was 88 people. The analytical prerequisite tests used in this study are the normality test, the homogeneity test, and the linearity test. To test the hypothesis using a simple linear regression test. The results of the study were: Variable X (Room Facilities) is in the unfavorable category with a percentage of 35%. Variable Y (Guest Satisfaction) is in the good category with a percentage of 38%. Based on a simple linear regression test f count of 76,276 with a significant 0.000 0.05, the room facilities variable can affect guest satisfaction with an R Square value of 0.470. Room facilities affect guest satisfaction significantly by 47% and are influenced by other factors by 53%. Based on the results of the study, it is recommended to further improve room facilities so that they become better and guest satisfaction increases.